Pengaruh Growth Opportunities, Konservatisme Akuntansi dan Ukuran Perusahaan terhadap Earnings Response Coefficient - Anisa Navin; Suwarno Suwarno (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to analyze the influence of growth opportunities, accounting conservatism, and company size on the earnings response coefficient. The sample for this research is mining companies listed on the Indonesia Stock Exchange (BEI), totaling 18 companies during the 2018-2022 period. Data was taken from the company's financial reports using a purposive sampling method. The classical assumption tests used consist of Data Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test. Meanwhile, the types of hypothesis testing used are the T Test (partial), F Test (simultaneous), and Determination Coefficient Test (R2) with multiple linear regression analysis. The research results show that growth opportunity and accounting conservatism have no effect on the earnings response coefficient, while company size has a negative effect on the earnings response coefficient.